A novel nano-porous alumina biomaterial with potential for loading with bioactive materials - Walpole, A; Xia, Z; Wilson, C; Wilshaw, P (Wiley, 2009)
Nano-porous alumina, with the potential for being loaded with bioactive materials, has been proposed as a novel material for coating implants. In this study, the shear strength of the interface between such nano-porous anodic aluminium oxide (AAO) coatings and titanium substrates, their biocompatibility, and their potential for pore loading have been investigated. An interface shear strength in excess of 29 MPa was obtained which is comparable with that of conventional plasma sprayed hydroxyapatite implant coatings. The viability and differentiation of MG63 osteoblastic cells co-cultured on the coating was found to be broadly comparable to that of similar cells co-cultured on conventional bioinert implant materials such as titanium and fully dense alumina. Extensive pore loading with silica nano-particles of different sizes and in different combinations was demonstrated throughout the thickness of AAO layers 1 μm and 60 μm thick. This work has demonstrated, that with suitable choice of pore filling materials, this novel coating might simultaneously combat infection, encourage bone regeneration, and secure fixation of the implant to bone.